Avaliação preliminar da previsão da capacidade de carga e do recalque de estacas pré-moldadas de concreto em perfis de solos granulares - Rodríguez, Yan Carlos Chiu (2015)
Prefabricated piles are a foundation of alternative indicated in situations where the neighborhood has no restrictions on the vibrations resulting from its implementation. In addition, soil profiles with low carrying capacity and surface extending deeper also indicate the choice of this alternative. In these cases and others, foundations Precast piles of concrete foundations can provide technically feasible and economically attractive. In this dissertation, it is made an analysis of the applicability of the main load capacity forecasting methods and repression of precast piles of reinforced concrete in typical granular soil profiles of commonly found in Fortaleza. The objective of this study is to evaluate whether predictions made by semi-empirical methods of load capacity and repression, carried out from polls to percussion (SPT) and granular soil profiles are consistent with reference to results of 7 load tests still performed. Furthermore, even if you want to evaluate whether evidence interrupted prematurely loads are able to be extrapolated to provide consistent breaking load forecasts. For that they were conducted polls percussion (SPT) and evidence of loads in some places situated in Fortaleza. The following were estimated values ​​of load capacity and settlement of each tested stake in load tests, and the workload, through semi-empirical methods, using values ​​of resistance index surveys to percussion (NSPT) corrected, and uncorrected, from the estimation of efficiency of used soundings. The predictions made from the values ​​of the resistance index (NSPT) provided fixed load capacity of estimates and the settlement of the piles evaluated more consistent. The semi-empirical methods that presented a greater agreement on forecasts of load capacities were Aoki and Velloso (1975) and Decourt and Lent (1982). The semi-empirical methods that showed a higher agreement in settlement predictions were Bowles (1979) and Poulos & Davis (1980).